SAT0125 Tenosynovitis in rheumatoid arthritis: prevalence and determinants of tenosynovitis detected in the sonar-ultrasound examination in the scqm cohort. (15th June 2017) - Micheroli, R; Scherrer, A; Brulhardt, L; Ziswiler, H; Zufferey, P; Möller, B; Ciurea, A; Tamborrini, G
Abstract : Background: Tenosynovitis is one of the common features of rheumatoid arthritis (RA). The diagnosis of tenosynovitis is frequently made clinically but for the detection of tenosynovitis, ultrasound (US) is more sensitive. US and MRI detected tenosynovitis is a predictor for unstable remission and erosive progression in RA . Objectives: The aim of this study was to assess the prevalence and determinants of TS detected in the SONAR (Swiss Sonography Group in Arthritis and Rheumatism) examinations in patients with Rheumatoid Arthritis in the SCQM Cohort. Methods: The SONAR ultrasound examination consists of a semi-quantitative score employing both multiplanar gray scale (B-mode) and Doppler-mode (PwD) and a TS composite score (grade 0–3). Pathologic TS was defined as TS grade 2–3. Characteristics of patients with and without TS are shown using standard descriptive methods. In a longitudinal sub-group the change in TS from no TS to pathologic TS or vice versa and DAS28 over time was categorized as "worse" (ΔDAS28 ≥2.1), "same" and "better" (ΔDAS28 ≤-2.1) and the correlation between change DAS28 and in tenosynovitis was evaluated. Results: 941 RA patients with TS score were available. 20% of included patients showed signs of TS. The presence of TS was associated with male gender and higher values of disease activity and physical function disability. Furthermore, 15% of patients in DAS28 Remission had sonographic TS. TS was less frequently observed in patients on biologic therapies (Table 1 ). The longitiudinal sub-group consisted of 348 patients. The correlation between change in DAS28 and change in TS was poor (polychoric correlation 0.28 [0.14, 0.43]). Conclusions: In the SCQM RA cohort TS is associated with male gender and an overall higher disease activity. One should actively look for TS even in RA patients in DAS28 remission. Disclosure of Interest: None declared